2017
DOI: 10.1080/13880209.2017.1357737
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of pomegranate flower in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages

Abstract: Context:Punica granatum L (Punicaceae) flower is an important diabetes treatment in oriental herbal medicine.Objective: This study investigates the inflammation effects of pomegranate flower (PFE) ethanol extract in LPS-induced RAW264.7 cells.Materials and methods: PFE (10, 25, 50, 100 μg/mL) was applied to 1 μg/mL LPS-induced RAW 264.7 macrophages in vitro. Levels of nitric oxide (NO), prostaglandin E2 (PGE2) and pro-inflammatory cytokines interleukin (IL)-1β (IL-1β), interleukin (IL)-6 (IL-6) and tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 26 publications
2
62
0
Order By: Relevance
“…NO, a well-known biomarker of inflammatory response induced by numerous inflammatory stimulation, contributes to tissue damage in various inflammatory and autoimmune diseases at high concentrations (Bogdan, 2001). Thus, NO is a valuable indicator in the screening of anti-inflammatory agents (Alvarez-Suarez et al 2017;Xu et al 2017). In this study, LPS, a component of the Gram-negative bacteria cell wall, was used to induce inflammatory response in macrophages through promoting the release of various inflammatory factors, including NO (Xu et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO, a well-known biomarker of inflammatory response induced by numerous inflammatory stimulation, contributes to tissue damage in various inflammatory and autoimmune diseases at high concentrations (Bogdan, 2001). Thus, NO is a valuable indicator in the screening of anti-inflammatory agents (Alvarez-Suarez et al 2017;Xu et al 2017). In this study, LPS, a component of the Gram-negative bacteria cell wall, was used to induce inflammatory response in macrophages through promoting the release of various inflammatory factors, including NO (Xu et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, excessive activation of aforementioned proinflammatory signalling and overproduction of these pro-inflammatory factors in macrophages is responsible for many inflammatory diseases, such as rheumatoid arthritis, cancer, atherosclerosis, diabetes and Alzheimer disease (McNelis and Olefsky 2014;Heppner et al 2015). Therefore, regulating the crucial proteins in these inflammatory signalling pathways or inhibiting the production of pro-inflammatory factors may serve to prevent or suppress a variety of inflammatory diseases (Pandurangan et al 2016;Alvarez-Suarez et al 2017;Xu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that PFE (10-100 μg/mL) significantly diminishes NO, PGE2, IL-6, IL-1β, and TNF-α levels. Additionally, PFE prevented extracellular signalregulated kinases (ERK), p38, JNK phosphorylation as well as nuclear factor kappa B (NF-κB) p65-subunit nuclear translocation in LPSstimulated RAW264.7 cells (Xu et al, 2017). Interestingly, it has been shown that pomegranate seed oil (25 μg/mL) considerably attenuates the levels of NO production, TNF-α, iNOS expression and caspase-3 activity following the LPS-induced inflammation in BV-2 murine microglial cell line (Rackova et al, 2014).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In contrast to pomegranate or its peel, pomegranate flower is less used in health studies. For example, P. granatum flower has played an important role in the treatment of diabetes in herbal medicine (Xu et al, 2017). PG could be used as a dietary supplement in the treatment of chronic diseases characterized by atherogenous lipoprotein profile, aggravated antioxidant status and impaired glucose metabolism and also in their prevention (Bagri et al, 2009).…”
Section: Activities the Extract Frommentioning
confidence: 99%